Mathematics education and language : interpreting hermeneutics and post-structuralism - Brown, Tony, 1946- (Mathematics education library, 1997)
Contemporary thinking on philosophy and the social sciences has been dominated by analyses that emphasise the importance of language in understanding societies and individuals functioning within them; important developments which have been under-utilised by researchers in mathematics education. This book reaches out to contemporary work in these broader fields; drawing on original sources in key areas such as Gadamer and Ricoeur's development of hermeneutics, Habermas' work in critical social theory, Schutz's social phenomenology, Saussure's linguistics and the post-structuralist analysis of Derrida, Foucault and Barthes. Through examining the writings of these major thinkers it is shown how language is necessarily instrumental in developing mathematical understanding; but a language that is in a permanent state of becoming, resisting stable connections to the ideas it locates.